ANALISIS POTENSI KEBANGKRUTAN KAFE DAN RESTO DI KOTA MALANG DENGAN MENGGUNAKAN METODE ZMIJEWSKI - Octavianus, Rony Joyo Negoro; Karina, Yusitha (Jurnal Ekonomi Modernisasi, 2016)
This research is conducted to evaluate the potential of bankruptcy related to cafes and restaurant in Malang city by applying Zmijewski method. The sampling method is using non-probability and also criteria sampling. The criteria of sampling method is cafes and restaurants that have been running for three years, owned the legal permit, and having the last three years financial reports, and the owner has agreed to permit the research. The X-Score resulted from seven cafes and restaurants that have been evaluated are under zero, which means they are financially healthy. However, there is a cafe and restaurant that has the probability of facing bankruptcy, but the score is still under the cut off value. The most contributing variable to be the cause of bankruptcy is the return on assets. Cafes and restaurants in Malang city will always be in a financially healthy condition if they have the ability to manage their assets and produce more profits.